Mine pit repairing method

By setting a double-layer support structure and a water-blocking gel layer in the coal gangue layer, the problems of the coal gangue layer being difficult to reuse and causing environmental pollution have been solved, and the stable repair and safe utilization of the coal gangue layer have been achieved.

CN120867756APending Publication Date: 2025-10-31SHENHUA SHENDONG COAL GRP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510742979.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-05
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

In existing technologies, after the coal gangue layer is solidified by injecting slurry materials, the coal gangue layer is difficult to reuse and there is a risk of metal ion leaching and spontaneous combustion, which leads to environmental pollution.

Method used

It adopts a double-layer support structure, including a first support layer and a water-blocking gel layer. The water-blocking gel layer absorbs excess moisture and prevents metal ions from seeping out. The second support layer isolates it from air contact. Combined with the drainage pipe design, it forms a sealed water storage space, reducing the risk of spontaneous combustion.

Benefits of technology

It has enabled the effective repair and reuse of coal gangue layers, significantly reduced metal ion precipitation, lowered the risk of spontaneous combustion, and ensured long-term stability and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005435162600000121
    Figure BDA0005435162600000121
  • Figure BDA0005435162600000171
    Figure BDA0005435162600000171
Patent Text Reader

Abstract

The invention relates to a mine pit repairing method. The method specifically comprises the following steps that (1) an impermeable layer is laid at the bottom of a leveled mine pit; (2) laying a coal gangue layer on the impermeable layer, and then laying a first supporting layer on the coal gangue layer; (3) injecting a layer of grouting base fluid on the first supporting layer, sequentially adding a part of volume of aqueous crosslinking fluid and alkali liquor containing fly ash into the grouting base fluid for reaction, and finally adding the residual aqueous crosslinking fluid to obtain a water-blocking gel layer; (4) laying a second supporting layer at a position 10-20 cm above the water-blocking gel layer, and installing a drainage pipe between the two supporting layers; and (5) a soil layer is laid on the second supporting layer, a crust material is sprayed, and repairing of the mine pit is completed. According to the invention, coal gangue resource utilization is taken as a core, through a multi-layer structural design, environmental protection, structural stability and ecological sustainability of mine pit restoration are realized, and an efficient and low-cost technical scheme is provided for treatment of mining wasteland.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the technical field of mine pit filling and relates to a mine pit repair method. Background Technology

[0002] Many open-pit mines are left behind during mining operations, and we must attach great importance to their management and restoration. Coal gangue, as a byproduct with high density and strong load-bearing capacity, can be used as backfill material to fill mine pits. Current technology involves injecting slurry materials into the coal gangue layer to solidify it, thereby reducing its contact with air, the risk of spontaneous combustion, and the leaching of metal ions, thus reducing environmental pollution. However, this method has the drawback of making the solidified coal gangue layer difficult to reuse and recycle. This approach reduces the land area occupied by coal gangue stockpiles, enabling its local utilization.

[0003] Therefore, existing technologies need to address the technical problem of how to effectively repair mine pits using coal gangue and facilitate the subsequent convenient and quick recycling of coal gangue. Summary of the Invention

[0004] To address the problems existing in the prior art, this invention discloses a mine pit remediation method. This invention comprises a first support layer and a second support layer, essentially a sealed space with a certain water storage function. Water that the water-resistant gel layer cannot absorb can be diverted out of the space between the first and second support layers using an existing water diversion device. This also prevents excessive water from entering the coal gangue layer through the first support layer, thereby avoiding significant leaching of metal ions from the coal gangue layer due to water seepage and environmental pollution. Furthermore, the second support layer also isolates the coal gangue layer from air, reducing the risk of spontaneous combustion.

[0005] To achieve the above objectives, the present invention adopts the following solution:

[0006] The first aspect of the present invention is to provide a mine pit repair method, comprising the following steps:

[0007] (1) Lay a seepage-proof layer at the bottom of the leveled mine pit;

[0008] (2) Lay a coal gangue layer on the seepage barrier layer, and then lay the first support layer on the coal gangue layer;

[0009] (3) Inject a layer of grouting base liquid into the first support layer, and add a portion of the volume of water-based crosslinking liquid to the grouting base liquid in sequence for reaction, and alkaline solution containing fly ash for reaction, and finally add the remaining water-based crosslinking liquid to obtain a water-blocking gel layer.

[0010] (4) Lay a second support layer 10-20cm above the water-resistant gel layer and install a drainage pipe between the two support layers;

[0011] (5) Lay a soil layer on the second support layer and spray crusting material to complete the mine pit repair.

[0012] The water-resistant gel layer will absorb water and expand, so when laying the second support layer 10-20cm above the water-resistant gel layer, some expansion space should be left for the water-resistant gel layer.

[0013] This invention first sets a first support layer on the coal gangue layer, and then sets a water-blocking gel layer on the first support layer. This water-blocking gel layer can fully absorb water from the second support layer or elsewhere. Even if it cannot absorb all the water, its water-blocking and water-stopping properties prevent excessive water from entering the first support layer, thus avoiding excessive water from entering the coal gangue layer through the first support layer. This prevents the significant leaching of metal ions from the coal gangue layer due to water infiltration, thus avoiding environmental pollution. In addition, this water-blocking gel layer has good compressive strength and is not easily damaged, and it also has excellent flame-retardant properties. Applying it above the coal gangue layer can provide secondary protection against combustion and pollution of the coal gangue layer. This invention also sets a second support layer on the water-blocking gel layer. The second support layer can prevent the water-blocking gel layer from being damaged by pressure from soil layers, etc., which helps maintain the performance stability of the water-blocking gel layer.

[0014] As a preferred implementation method,

[0015] Step (1), the impermeable layer consists of a clay layer, a bentonite layer and a polyethylene LDPE membrane layer from bottom to top.

[0016] Preferably, in the impermeable layer, the thickness of the clay layer is 30-40cm; the thickness of the bentonite layer is 20-30cm; and the thickness of the polyethylene LDPE membrane layer is 1.0-1.5mm.

[0017] Step (5), the crusting material, includes the following raw materials in parts by weight:

[0018] Sodium alginate is 0.5–0.52 parts;

[0019] Polyvinyl alcohol is 4 to 5.3 parts;

[0020] Glycerin: 5-6 parts;

[0021] Sodium tripolyphosphate is 0.12–0.13 parts;

[0022] The amount of calcium chloride is 0.05–0.06 parts;

[0023] Sodium dodecylbenzenesulfonate is 0.5 to 0.8 parts.

[0024] The amount of crusting material sprayed should be 2%–3% of the soil mass.

[0025] In the crust material system prepared by this invention, sodium alginate and polyvinyl alcohol are the reaction substrates, providing crosslinking sites for the subsequent polymerization of glycerol, sodium trimetaphosphate, and calcium chloride. Sodium trimetaphosphate acts as a crosslinking agent to complete the chemical crosslinking between polymers, and then forms a network structure through crosslinking between calcium ions and sodium alginate ions. Sodium dodecyl sulfate is an emulsifier that can effectively improve the solubility and wetting properties of the material. Sodium alginate and polyvinyl alcohol are monomers that form the network matrix, giving the material adhesiveness and adsorption properties, and enhancing its stability and mechanical properties.

[0026] In a preferred embodiment, the amount of crust material added is 2-3% of the soil mass;

[0027] This invention, based on existing conventional soil, involves spraying a crusting material onto non-planted areas of the soil, which can effectively prevent soil erosion by wind.

[0028] As a preferred embodiment, the method for preparing the crust material includes the following steps:

[0029] (a) Under heating conditions, polyvinyl alcohol is added to water and mixed evenly to obtain a polyvinyl alcohol solution;

[0030] (b) Under heating conditions, sodium alginate was added to a solution of polyvinyl alcohol and mixed thoroughly, and glycerol was added and mixed thoroughly to obtain a mixture;

[0031] (c) Add alkali solution to adjust the pH of the mixture, continue stirring for a period of time, first add sodium trimetaphosphate and mix well, add water, then add calcium chloride solution and mix well; finally add sodium dodecylbenzenesulfonate and mix well to obtain the crust material.

[0032] As a preferred implementation method,

[0033] Step (a),

[0034] The heating temperature is 90-95℃;

[0035] Step (b),

[0036] The heating temperature is 40-55℃;

[0037] The sodium alginate solution was added to the polyvinyl alcohol solution and mixed for 2.5-3.5 hours.

[0038] The time for adding glycerin and mixing thoroughly is 0.5-1.5 hours.

[0039] As a preferred implementation method,

[0040] Step (c),

[0041] The alkaline solution is a sodium hydroxide solution;

[0042] Adjust the pH to 9.5-10.5;

[0043] Continue stirring for 25-35 minutes;

[0044] The alkaline solution is a sodium hydroxide solution with a concentration of 0.9-1.2 mol / L;

[0045] The time for adding sodium trimetaphosphate and mixing thoroughly is 2.5-3.5 hours;

[0046] Add water to make the volume of the solution 230-260 ml;

[0047] The volume of the solution containing calcium chloride is 23-26 ml.

[0048] According to the preparation steps of the crust material, sodium alginate, polyvinyl alcohol, glycerol, sodium trimetaphosphate and calcium chloride react in the following steps: (1) Polyvinyl alcohol is completely dissolved in water to form a polyvinyl alcohol aqueous solution. The polyvinyl alcohol molecular chains form cross-linking points through interchain hydroxyl hydrogen bonds. After sodium alginate is dissolved in the polyvinyl alcohol aqueous solution, the physical cross-linking between the hydroxyl groups of polyvinyl alcohol and sodium alginate will form intermolecular hydrogen bonds, thus initially forming a three-dimensional physical cross-linking network structure. (2) Glycerol itself contains a large number of hydroxyl groups, which will generate strong intramolecular and intermolecular hydrogen bonds with the hydroxyl groups of sodium alginate and polyvinyl alcohol, increasing the intermolecular forces, which is conducive to the aggregation of molecular chains, has a certain adhesion, and increases the viscosity of the material. Due to the strong hydrogen bond effect, a three-dimensional physical cross-linking network structure of SA-PVA-Gly is formed. (3) Under alkaline conditions, the added sodium trimetaphosphate can undergo a chemical cross-linking reaction with the hydroxyl groups in the sodium alginate and polyvinyl alcohol polymers, promoting the formation of a network structure between high molecular weight polymers. The network structure formed by this chemical cross-linking has a strong cohesive force. It can effectively bind dust particles. When water-soluble calcium salts are introduced into a polymer solution, the calcium ions in calcium chloride can coordinate with the G segments and the carboxyl groups (-COO-) of adjacent G segments in the sodium alginate molecular chain, thereby causing physical cross-linking of the sodium alginate linear molecular chain to form an SA network through an "egg box" structure.

[0049] As a preferred implementation method,

[0050] Step (3),

[0051] A 5-10cm thick layer of grouting base liquid is injected on the first support layer. Then, 75%-90% of the total volume of the water-based crosslinking liquid is added to the grouting base liquid for reaction. Then, an alkaline solution containing fly ash is added for reaction. Finally, the remaining water-based crosslinking liquid is added to obtain the water-resistant gel layer.

[0052] As a preferred implementation method,

[0053] The grouting base liquid in step (3) is obtained by mixing hydrophilic polyurethane prepolymer and modified coal-based solid waste suspension evenly.

[0054] Preferably, the mass ratio of the hydrophilic polyurethane prepolymer to the modified coal-based solid waste suspension is 1:(0.1-0.3).

[0055] As a preferred implementation method,

[0056] The preparation method of the hydrophilic polyurethane prepolymer includes the following steps:

[0057] In a protective atmosphere, polyether polyol and isocyanate are mixed and then heated to react, yielding the hydrophilic polyurethane prepolymer.

[0058] Preferably, the polyether polyol is dehydrated at 110-120℃ for 1.5-2.5 hours before use;

[0059] The molar ratio of -NCO in the isocyanate to -OH in the polyether polyol is (5-8):1;

[0060] The temperature of the heating reaction is 75-82℃, and the reaction time is 2.5h-3h;

[0061] The polyether polyol is selected from polyether polyols with a functionality of 3 and a molecular weight of approximately 4000-10000; preferably BD3-9000A.

[0062] The isocyanate is selected from diphenylmethane diisocyanate (MDI).

[0063] As a preferred implementation method,

[0064] The modified coal-based solid waste suspension includes a mixture of modified fly ash, modified coal gangue, and organic solvents.

[0065] Preferably,

[0066] Modified fly ash is fly ash modified with a silane coupling agent;

[0067] The modified coal gangue is coal gangue modified with a silane coupling agent;

[0068] The organic solvent is ethyl acetate or methyl acetate;

[0069] The mass ratio of unmodified fly ash to unmodified coal gangue is 1:(1.2-1.5);

[0070] The mass ratio of modified fly ash to organic solvent is (1-2):100.

[0071] As a preferred implementation method,

[0072] The preparation method of modified coal gangue includes the following steps:

[0073] Coal gangue was added to a water-alcohol mixture, then a silane coupling agent was added. After hydrolysis, the mixture was vacuum dried, ground, and coal gangue with a particle size of 2-4 mm modified with the silane coupling agent was selected.

[0074] The preparation method of modified fly ash includes the following steps:

[0075] Fly ash was added to a water-alcohol mixture, then a silane coupling agent was added. After hydrolysis, the mixture was vacuum dried and ground to obtain fly ash modified with a silane coupling agent.

[0076] Preferably,

[0077] The silane coupling agent is KH-550 or KH-560;

[0078] The aqueous-ethanol mixture is a mixture of water and ethanol with a volume ratio of 1:(8-9).

[0079] The mass ratio of the coal gangue to the water-alcohol mixture is 1:(10-15);

[0080] The mass ratio of the fly ash to the water-alcohol mixture is 1:(10-15);

[0081] The mass ratio of the silane coupling agent to the water-alcohol mixture is 1:(40-50);

[0082] The hydrolysis reaction takes 50-60 minutes.

[0083] Modified fly ash, modified coal gangue, and organic solvent are mixed evenly to obtain a modified coal-based solid waste suspension.

[0084] As a preferred implementation method,

[0085] The aqueous crosslinking liquid in step (3) includes sodium alginate and water, with a mass ratio of sodium alginate to water of 1:(100-150).

[0086] Step (3), the mass ratio of the hydrophilic polyurethane prepolymer to the aqueous crosslinking liquid is 1:(15-25);

[0087] As a preferred implementation method,

[0088] Step (3), the alkaline solution containing fly ash includes fly ash, alkali and ethanol; wherein, the mass ratio of fly ash to alkali is 1:4-8; the concentration of alkali in ethanol is 2-4 mol / L; and the alkali is sodium hydroxide or potassium hydroxide.

[0089] The mass ratio of the hydrophilic polyurethane prepolymer used in the injection base to the alkaline solution containing fly ash is 1:(0.5-1).

[0090] As a preferred implementation method,

[0091] The drainage pipes are evenly distributed between the first support layer and the second support layer, with a pipe spacing of 1-2m, and are used to guide water that has not been absorbed by the water-blocking gel layer.

[0092] As a preferred implementation method,

[0093] Both the first and second support layers are formed by mixing and curing fly ash, lime, and cement in a mass ratio of (45-70):(18-30):(15-20) with water glass (4-7% of the cement mass), with a thickness of 10-20 cm. The liquid-to-solid ratio of the slurry is 0.65-0.85.

[0094] As a preferred implementation method,

[0095] In step (5), the thickness of the soil layer is 100-150cm, and the amount of the crust material sprayed is 2%-3% of the soil mass, forming a wind-erosion resistant surface layer with a thickness of 0.5-1mm.

[0096] In a preferred embodiment, the water-blocking gel layer comprises a quadruple gel network:

[0097] A gel formed by the reaction of S1 polyurethane prepolymer with water;

[0098] Electrite / CSH gel generated from the hydration of S2 coal-based solid waste;

[0099] S3 mineral gel formed by the reaction of fly ash and alkaline solution in the pores.

[0100] S4 sodium alginate crosslinked with calcium ions gel.

[0101] The water-blocking gel layer of this invention contains at least four types of gels: the first is a gel formed by the reaction of polyurethane prepolymer with water; the second is a gel formed by the hydration reaction of coal-based solid waste with water or with water under the action of alkali, embedded in the gel formed by the reaction of polyurethane prepolymer with water; the third is a hydrate and gel formed by the hydration reaction of fly ash, which enters the pores of the gel formed by the reaction of polyurethane prepolymer with water, with alkali and water; and the fourth is sodium alginate distributed in the aqueous crosslinking liquid in the gel formed by the reaction of polyurethane prepolymer with water, which can further crosslink with calcium ions overflowing from coal gangue or fly ash to form a gel; the specific reaction process is as follows:

[0102] This invention incorporates a modified coal-based solid waste suspension into a hydrophilic polyurethane prepolymer. This modified coal-based solid waste suspension can, on the one hand, reduce the viscosity of the hydrophilic polyurethane prepolymer, preventing it from becoming too viscous and difficult to grout; on the other hand, it can introduce coal-based solid waste into the hydrophilic polyurethane prepolymer. When the hydrophilic polyurethane prepolymer and the modified coal-based solid waste suspension grouting base liquid are injected into the matrix to be grouted, a portion of the volume of aqueous crosslinking liquid is first added for reaction. The isocyanate groups in the hydrophilic polyurethane prepolymer react with water to crosslink and solidify into a water-insoluble primary gel. The coal-based solid waste and sodium alginate from the aqueous crosslinking liquid are fixed and dispersed in the primary gel. During the formation of the primary gel, CO2 gas is released simultaneously. The generated gas propels the grout to continue diffusing deeper into the cracks. Simultaneously, the released CO2 gas leaves pores in the primary gel due to diffusion, with some overflowing and some remaining within the primary gel. After the primary gel is formed, an alkaline solution containing fly ash is added. This alkaline solution does not contain water and therefore does not react significantly with the hydrophilic polyurethane prepolymer, but it can penetrate the pores of the primary gel, where further fly ash reaction occurs. The hydration reaction with the alkaline solution is followed by the addition of the remaining aqueous crosslinking liquid, which allows the hydrophilic polyurethane prepolymer to continue reacting, further increasing the gelation degree of the hydrophilic polyurethane prepolymer gel. This also allows the alkaline solution to be further encapsulated within the initial gel. Since the alkali in the alkaline solution is in excess relative to the fly ash, it can react with the fly ash to generate high-strength ettringite and CSH gel, which fill the pores of the initial gel. Furthermore, it can diffuse within the gel and undergo a slow hydration reaction with the coal-based solid waste (i.e., coal-based solid waste introduced into the initial gel from the modified coal-based solid waste suspension) fixed in the initial gel. It can also react with the hydrophilic polyurethane prepolymer to generate high-strength ettringite and CSH gel, which fill the initial gel, thereby enhancing the compressive strength of the gel after the polyurethane prepolymer reacts with water and reducing the shrinkage of the gel after the polyurethane prepolymer reacts with water. In addition, when the fly ash or coal gangue of the present invention reacts with water or with water under the action of alkaline solution, some calcium ions will also be dissolved. These calcium ions can form coordination with the sodium alginate molecular chain, thereby further crosslinking the sodium alginate in the gel after the polyurethane prepolymer reacts with water. This can also enhance the compressive strength of the gel after the polyurethane prepolymer reacts with water and reduce the shrinkage of the gel after the polyurethane prepolymer reacts with water.

[0103] As can be seen, the water-blocking gel layer of the present invention contains at least four types of gels: the first type is a gel formed by the reaction of polyurethane prepolymer with water; the second type is a gel formed by the hydration reaction of coal-based solid waste with water or with water under the action of alkali, which is embedded in the gel formed by the reaction of polyurethane prepolymer with water; the third type is a hydrate and gel formed by the hydration reaction of fly ash, which enters the pores of the gel formed by the reaction of polyurethane prepolymer with water, with alkali and water; and the fourth type is sodium alginate distributed in the aqueous crosslinking liquid in the gel formed by the reaction of polyurethane prepolymer with water, which can further crosslink with calcium ions overflowing from coal gangue or fly ash to form a gel.

[0104] In existing technologies, a slurry material is injected into the coal gangue layer to solidify it, thereby reducing the contact between the coal gangue layer and air, reducing the risk of spontaneous combustion, and reducing the leaching of metal ions from the coal gangue, thus reducing environmental pollution. However, this method has the problem that the solidified coal gangue layer is difficult to reuse and recycle. To solve this problem, this invention first sets a first support layer on the coal gangue layer, and then sets a water-blocking gel layer on the first support layer. This water-blocking gel layer can fully absorb water from the second support layer or elsewhere. Even if it cannot absorb all the water, its water-blocking and water-stopping properties can prevent excessive water from entering the first support layer, thereby preventing excessive water from entering the coal gangue layer from the first support layer. This avoids the large-scale leaching of metal ions from the coal gangue layer due to water penetration, which would pollute the environment.

[0105] In addition, the water-resistant gel layer has good compressive strength and is not easily damaged, and it also has a good flame retardant effect. Applying it above the coal gangue layer can provide secondary protection to reduce the combustion and pollution of the coal gangue layer.

[0106] This invention also includes a second support layer on top of the water-blocking gel layer. This second support layer prevents the water-blocking gel layer from being damaged by pressure from the soil layer, thus helping to maintain the stability of its performance. Furthermore, the first and second support layers act as a sealed space, providing a certain water storage capacity. Water that the water-blocking gel layer cannot absorb can be diverted out of the space between the first and second support layers using existing water diversion devices. This also prevents excessive water from entering the coal gangue layer from the first support layer, thereby avoiding significant leaching of metal ions from the coal gangue layer due to water infiltration and environmental pollution.

[0107] Furthermore, the second support layer can also isolate the coal gangue layer from air, reducing the risk of spontaneous combustion.

[0108] Compared with the prior art, the advantages of the present invention are:

[0109] This invention solves the land occupation and environmental pollution problems caused by coal gangue accumulation by using coal gangue as the core material for mine backfilling. The water-blocking gel layer encapsulates the coal gangue through a quadruple gel network (polyurethane gel, coal-based solid waste hydration gel, pore-filling mineral gel, and sodium alginate crosslinking gel), significantly reducing metal ion release (curing rate ≥99.7% in the examples) and isolating it from air contact, thus reducing the risk of spontaneous combustion. A double-layer support layer (fly ash-lime-cement composite material) and drainage pipe design form a sealed water storage space, achieving dynamic moisture regulation by combining the water-blocking gel's water absorption and expansion characteristics. The support layer is 10-20cm thick, has high compressive strength, and prevents the gel layer from being damaged by the pressure of the upper soil layer, ensuring long-term stability. Detailed Implementation

[0110] Preparation Example 1

[0111] Raw material preparation:

[0112] A: The preparation method of hydrophilic polyurethane prepolymer includes the following steps:

[0113] In a protective atmosphere (nitrogen), polyether polyol and isocyanate are mixed and reacted at a controlled temperature to obtain the hydrophilic polyurethane prepolymer. The polyether polyol is dehydrated at 120°C for 2 hours before use. The molar ratio of -NCO (isocyanate group (-NCO)) to -OH of the polyether polyol is 5:1. The reaction temperature is 82°C, and the reaction time is 2.5 hours. The polyether polyol is selected from BD3-9000A (purchased from Jiangsu Bade Polyurethane Co., Ltd.), which has a functionality of 3 and a molecular weight of approximately 9000. The isocyanate is selected from diphenylmethane diisocyanate (MDI).

[0114] B: The preparation method of modified coal gangue includes the following steps:

[0115] Coal gangue was added to a water-ethanol mixture (the volume ratio of water to ethanol was 1:9), and then silane coupling agent KH-550 was added. The mass ratio of silane coupling agent to water-ethanol mixture was 1:50. After hydrolysis reaction for 50 min, the mixture was vacuum dried at 60℃ for 12 h and ground for 3 h. Coal gangue modified with silane coupling agent with a particle size of 2 mm was selected.

[0116] C: The preparation method of modified fly ash includes the following steps:

[0117] Fly ash was added to a water-ethanol mixture (where the volume ratio of water to ethanol was 1:8), and then silane coupling agent KH-550 was added. The mass ratio of silane coupling agent to water-ethanol mixture was 1:50. After hydrolysis reaction for 50 min, the mixture was vacuum dried at 60℃ for 12 h and then ground for 1 h to obtain fly ash modified with silane coupling agent.

[0118] D: Mix the modified fly ash, modified coal gangue and organic solvent (ethyl acetate) evenly to obtain a modified coal-based solid waste suspension.

[0119] The hydrophilic polyurethane prepolymer and the modified coal-based solid waste suspension are mixed evenly to obtain the grouting base liquid.

[0120] E: Aqueous crosslinking solution: Sodium alginate and water are mixed evenly to obtain an aqueous crosslinking solution, wherein the mass ratio of sodium alginate to water is 1:100.

[0121] F: Alkali solution containing fly ash: Alkali solution containing fly ash is obtained by mixing fly ash, alkali and ethanol evenly; wherein, the mass ratio of fly ash to alkali is 1:8; the concentration of alkali in ethanol is 4 mol / L; the alkali is potassium hydroxide.

[0122] Preparation Example 2

[0123] Raw material preparation:

[0124] A: The preparation method of hydrophilic polyurethane prepolymer includes the following steps:

[0125] In a protective atmosphere (nitrogen), polyether polyol and isocyanate are mixed and reacted at a controlled temperature to obtain the hydrophilic polyurethane prepolymer. The polyether polyol is dehydrated at 120°C for 2 hours before use. The molar ratio of -NCO (isocyanate group (-NCO)) to -OH of the polyether polyol is 8:1. The reaction temperature is 75°C, and the reaction time is 3 hours. The polyether polyol is selected from BD3-9000A (purchased from Jiangsu Bade Polyurethane Co., Ltd.), which has a functionality of 3 and a molecular weight of approximately 9000. The isocyanate is selected from diphenylmethane diisocyanate (MDI).

[0126] B: The preparation method of modified coal gangue includes the following steps:

[0127] Coal gangue was added to a water-ethanol mixture (the volume ratio of water to ethanol was 1:8), and then silane coupling agent KH-560 was added. The mass ratio of silane coupling agent to water-ethanol mixture was 1:40. After hydrolysis, the mixture was dried under vacuum at 60°C for 12 hours after 60 minutes of hydrolysis, and then ground for 2 hours. Coal gangue modified with silane coupling agent with a particle size of 4 mm was selected.

[0128] C: The preparation method of modified fly ash includes the following steps:

[0129] Fly ash was added to a water-ethanol mixture (where the volume ratio of water to ethanol was 1:8), and then silane coupling agent KH-560 was added. The mass ratio of silane coupling agent to water-ethanol mixture was 1:40. After hydrolysis reaction for 60 min, the mixture was vacuum dried at 60℃ for 12 h and ground for 0.5 h to obtain fly ash modified with silane coupling agent.

[0130] D: Mix the modified fly ash, modified coal gangue and organic solvent (methyl acetate) evenly to obtain a modified coal-based solid waste suspension.

[0131] The hydrophilic polyurethane prepolymer and the modified coal-based solid waste suspension are mixed evenly to obtain the grouting base liquid.

[0132] E: Aqueous crosslinking solution: Sodium alginate and water are mixed evenly to obtain an aqueous crosslinking solution, wherein the mass ratio of sodium alginate to water is 1:150.

[0133] F: Alkali solution containing fly ash: Alkali solution containing fly ash is obtained by uniformly mixing fly ash, alkali and ethanol; wherein, the mass ratio of fly ash to alkali is 1:4; the concentration of alkali in ethanol is 2 mol / L; the alkali is sodium hydroxide.

[0134] Preparation Example 3

[0135] A method for preparing a crust material includes the following steps:

[0136] (1) Preparation of PVA solution: Place a 500ml conical flask in a water bath, slowly and evenly add polyvinyl alcohol (PVA), adjust the temperature to 95℃ and prepare PVA aqueous solution by magnetic stirring for 3h.

[0137] (2) Synthesis of main materials: Adjust the temperature of the water bath to 50°C. After the temperature stabilizes at 50°C, slowly add sodium alginate (SA) powder to the PVA solution in portions and stir magnetically for 3 hours. Then add glycerol (Gly) and stir magnetically for 1 hour until dissolved.

[0138] (3) Crosslinking of polymer chains: The pH of the solution was adjusted to 10 by adding 1.0M NaOH dropwise; after 30 minutes, sodium trimetaphosphate (STMP) was added to the solution and magnetically stirred for 3 hours until completely dissolved; under alkaline conditions, the phosphate groups of STMP reacted with the hydroxyl groups of PVA and SA to form new bonds through chemical crosslinking, and water was added to 250 ml; then 25 ml of calcium chloride solution was added and magnetically stirred until dissolved. Finally, sodium dodecylbenzenesulfonate was added and magnetically stirred until dissolved.

[0139] The synthesis mechanism of the crust material of the present invention includes: physical cross-linking between the hydroxyl groups of polyvinyl alcohol, the hydroxyl groups of sodium alginate and glycerol to form hydrogen bonds; chemical cross-linking reaction between sodium trimetaphosphate and the hydroxyl groups in the sodium alginate and polyvinyl alcohol polymers; and ionic cross-linking between the linear molecular chains of sodium alginate and calcium chloride to form an egg-box structure.

[0140] The amounts of sodium alginate, polyvinyl alcohol, glycerol, sodium trimetaphosphate, calcium chloride, and sodium dodecylbenzenesulfonate added in the above preparation examples are shown in Table 1.

[0141] Table 1

[0142] Preparation Example PVA(g) SA(g) Gly(g) STMP(g) <![CDATA[CaCl2(g)]]> Dodecylbenzenesulfonic acid (g) 3 5.2 0.51 5.3 0.13 0.05 0.5

[0143] After the crusting material of the present invention binds a large number of soil particles, the gaps between the particles become tighter, and the soil surface becomes flatter and denser. The cross-section of the crusting material film of the present invention at 500x magnification clearly shows the formed network structure, indicating that the monomers have formed a three-dimensional structure under the influence of the cross-linking agent.

[0144] The properties of the crust material prepared in the above preparation example were tested, and the results are shown in Table 2.

[0145] Viscosity test: Viscosity is one of the important performance indicators of soil crust materials, used to measure the binding effect of the crust material on soil particles. This test determines the viscosity of the sample according to the rotation method in GB / T10247-2008, using a rotational viscometer (RheolabQC).

[0146] Hardness testing: The hardness of a material reflects its compressive strength after a crust forms on topsoil, and is one of the important indicators for testing the performance of crust materials. An LX-A type Shore hardness tester was used to test the hardness of the samples.

[0147] Water retention test: The water retention rate is used to evaluate the water retention performance of the crust material. The higher the water retention rate, the stronger the water retention capacity. The test steps are as follows:

[0148] (1) Prepare 18 samples of 600g soil fugitive dust and dry them in a forced-air drying oven (temperature control range: 10-300℃) at 75℃.

[0149] (2) Place the treated soil sample (600±0.05g) into a petri dish with an inner diameter of 12.5±0.1cm and a height of 63mm.

[0150] (3) Spray the prepared compound solutions of different concentrations evenly onto the surface of the soil dust sample. After 48 hours of complete solidification, record the weight of the sample. The water retention rate is calculated according to the following formula.

[0151]

[0152] In the formula, MRR (%) is the water retention rate, and m1 (g) is the weight of the petri dish after spraying the crusting material;

[0153] m2(g) is the weight of the culture dish measured after 48 hours;

[0154] m3(g) represents the weight of the sprayed crusting material.

[0155] Permeability test: The experiment was conducted according to the permeation rate method in GB / T16913-2008 "Test Methods for Physical Properties of Dust", and the wetting rate was used to reflect the material's permeability to soil.

[0156] Table 2

[0157] Preparation Example Viscosity (cP) Hardness (HA) Permeation rate (mm / min) Water retention rate (%) 3 79.60 78.80 0.50 96.80

[0158] The viscosity of the crusting material prepared by this invention is 70-85 cP, which not only ensures the adhesion of the crusting material to soil particles but also avoids clogging problems during spraying. Given the low rainfall in mining areas, the crusting material prepared by this invention exhibits high anti-evaporation performance and good water retention. The crusting material prepared by this invention also has good hardness, which improves the mechanical properties and anti-interference ability of the soil solidification layer. The penetration rate of the crusting material prepared by this invention is 0.4-0.6 mm / min, which is moderate. Too slow a penetration rate will affect the effective wetting depth of the crusting material, thus affecting the application effect; while too fast a penetration rate will affect the hardness of the film, resulting in the inability to form a complete and stable solidified layer, thereby reducing the material's consolidation capacity. In summary, the crusting material prepared by this invention has excellent overall performance.

[0159] Example 1

[0160] (1) Level the bottom of the mine pit and lay an impermeable layer at the bottom of the leveled mine pit; wherein the impermeable layer consists of a 35cm clay layer, a 30cm bentonite layer and a 1.0mm polyethylene LDPE film layer from bottom to top.

[0161] (2) Lay a coal gangue layer on the seepage barrier layer. The height of the coal gangue layer is 100cm. Then lay the first support layer on the coal gangue layer. Inject a layer of grouting base liquid on the first support layer. Then add water crosslinking liquid that accounts for 90% of the total volume of water crosslinking liquid. After reacting for 1 minute with the water crosslinking liquid, add alkaline solution containing fly ash and react for 2 hours. Then add the remaining water crosslinking liquid to obtain a water-blocking gel layer.

[0162] Preparation of the water-blocking gel layer: The water-blocking gel layer is prepared by reacting the following raw materials: hydrophilic polyurethane prepolymer, modified coal-based solid waste suspension, aqueous crosslinking liquid, and alkaline solution containing fly ash, using the raw materials prepared in Preparation Example 1; wherein, the mass ratio of hydrophilic polyurethane prepolymer to modified coal-based solid waste suspension is 1:0.2; the mass ratio of aqueous crosslinking liquid to hydrophilic polyurethane prepolymer is 1:18; and the mass ratio of hydrophilic polyurethane prepolymer to alkaline solution containing fly ash is 1:0.8.

[0163] (3) A second support layer was laid 15 cm above the water-resistant gel layer. The first and second support layers were obtained by solidifying a slurry made of fly ash, lime, cement, water glass and water. The mass ratio of fly ash, lime and cement was 60:22:20. The amount of water glass added was 6% of the cement mass. The liquid-solid ratio of the slurry was 0.75. The thickness of the support layer was 20 cm. Then a soil layer was laid on the support layer. The crust material prepared in Example 3 was sprayed on the soil layer. The amount of spraying was 2.5% of the soil mass, and the mine pit was repaired.

[0164] Example 2

[0165] (1) Level the bottom of the mine pit and lay an impermeable layer at the bottom of the leveled mine pit; wherein the impermeable layer consists of a 35cm clay layer, a 30cm bentonite layer and a 1.0mm polyethylene LDPE film layer from bottom to top.

[0166] (2) Lay a coal gangue layer on the seepage barrier layer. The height of the coal gangue layer is 100cm. Then lay the first support layer on the coal gangue layer. Inject a layer of grouting base liquid on the first support layer. Then add water crosslinking liquid that accounts for 85% of the total volume of water crosslinking liquid. After reacting for 2 minutes, add alkaline solution containing fly ash and react for 1.5 hours. Then add the remaining water crosslinking liquid to obtain a water-blocking gel layer.

[0167] Preparation of the water-blocking gel layer: The water-blocking gel layer is prepared by reacting the following raw materials: hydrophilic polyurethane prepolymer, modified coal-based solid waste suspension, aqueous crosslinking liquid, and alkaline solution containing fly ash, using the raw materials prepared in Preparation Example 1; wherein, the mass ratio of hydrophilic polyurethane prepolymer to modified coal-based solid waste suspension is 1:0.3; the mass ratio of aqueous crosslinking liquid to hydrophilic polyurethane prepolymer is 1:12; and the mass ratio of hydrophilic polyurethane prepolymer to alkaline solution containing fly ash is 1:0.5.

[0168] (3) A second support layer was laid 18 cm above the water-resistant gel layer. The first and second support layers were obtained by solidifying a slurry made of fly ash, lime, cement, water glass and water. The mass ratio of fly ash, lime and cement was 60:22:20. The amount of water glass added was 6% of the cement mass. The liquid-solid ratio of the slurry was 0.75. The thickness of the support layer was 20 cm. Then a soil layer was laid on the support layer. The crust material prepared in Example 3 was sprayed on the soil layer. The amount of spraying was 3% of the soil mass, and the mine pit repair was completed.

[0169] Example 3

[0170] (1) Level the bottom of the mine pit and lay an impermeable layer at the bottom of the leveled mine pit; wherein the impermeable layer consists of a 35cm clay layer, a 30cm bentonite layer and a 1.0mm polyethylene LDPE film layer from bottom to top.

[0171] (2) Lay a coal gangue layer on the seepage barrier layer. The height of the coal gangue layer is 100cm. Then lay the first support layer on the coal gangue layer. Inject a layer of grouting base liquid on the first support layer. Then add water crosslinking liquid that accounts for 90% of the total volume of water crosslinking liquid. After reacting for 3 minutes, add alkaline solution containing fly ash and react for 1.5 hours. Then add the remaining water crosslinking liquid to obtain a water-blocking gel layer.

[0172] Preparation of the water-blocking gel layer: The water-blocking gel layer is prepared by reacting the following raw materials: hydrophilic polyurethane prepolymer, modified coal-based solid waste suspension, aqueous crosslinking liquid, and alkaline solution containing fly ash, using the raw materials prepared in Preparation Example 2; wherein, the mass ratio of hydrophilic polyurethane prepolymer to modified coal-based solid waste suspension is 1:0.25; the mass ratio of aqueous crosslinking liquid to hydrophilic polyurethane prepolymer is 1:10; and the mass ratio of hydrophilic polyurethane prepolymer to alkaline solution containing fly ash is 1:1.

[0173] (3) A second support layer was laid 10 cm above the water-resistant gel layer. The first and second support layers were obtained by solidifying a slurry made of fly ash, lime, cement, water glass and water. The mass ratio of fly ash, lime and cement was 60:22:20. The amount of water glass added was 6% of the cement mass. The liquid-solid ratio of the slurry was 0.75. The thickness of the support layer was 20 cm. Then a soil layer was laid on the support layer. The crust material prepared in Example 3 was sprayed on the soil layer. The amount of spraying was 2.5% of the soil mass, and the mine pit was repaired.

[0174] Example 4

[0175] (1) Level the bottom of the mine pit and lay an impermeable layer at the bottom of the leveled mine pit; wherein the impermeable layer consists of a 35cm clay layer, a 30cm bentonite layer and a 1.0mm polyethylene LDPE film layer from bottom to top.

[0176] (2) Lay a coal gangue layer on the seepage barrier layer with a height of 100cm; then lay the first support layer on the coal gangue layer, inject a layer of grouting base liquid on the first support layer, then add water crosslinking liquid accounting for 75% of the total volume of water crosslinking liquid, react for 2 minutes after adding water crosslinking liquid, then add alkaline solution containing fly ash and react for 1 hour, then add the remaining water crosslinking liquid to obtain a water-blocking gel layer.

[0177] Preparation of the water-blocking gel layer: The water-blocking gel layer is prepared by reacting the following raw materials: hydrophilic polyurethane prepolymer, modified coal-based solid waste suspension, aqueous crosslinking liquid, and alkaline solution containing fly ash, using the raw materials prepared in Preparation Example 2; wherein, the mass ratio of hydrophilic polyurethane prepolymer to modified coal-based solid waste suspension is 1:0.1; the mass ratio of aqueous crosslinking liquid to hydrophilic polyurethane prepolymer is 1:15; and the mass ratio of hydrophilic polyurethane prepolymer to alkaline solution containing fly ash is 1:0.6.

[0178] (3) A second support layer was laid 20 cm above the water-resistant gel layer. The first and second support layers were obtained by solidifying a slurry made of fly ash, lime, cement, water glass and water. The mass ratio of fly ash, lime and cement was 60:22:20. The amount of water glass added was 6% of the cement mass. The liquid-solid ratio of the slurry was 0.75. The thickness of the support layer was 20 cm. Then a soil layer was laid on the support layer. The crust material prepared in Example 3 was sprayed on the soil layer. The amount of spraying was 2.5% of the soil mass, and the mine pit was repaired.

[0179] Comparative Example 1

[0180] It uses the same preparation method as Example 1, except that sodium alginate is not added to the aqueous crosslinking liquid in the preparation of the water-blocking gel layer, and pure water of equal mass is used instead of sodium alginate.

[0181] Comparative Example 2

[0182] It uses the same preparation method as Example 1, except that in the preparation of the water-blocking gel layer, no alkali and fly ash are added to the alkaline solution containing fly ash, and an equal mass of ethanol is used instead of alkali and fly ash.

[0183] Comparative Example 3

[0184] It uses the same preparation method as Example 1, except that in the preparation of the water-blocking gel layer, fly ash is not added to the alkaline solution containing fly ash, and an equal mass of ethanol is used instead of fly ash.

[0185] Comparative Example 4

[0186] It uses the same preparation method as Example 1, except that in the preparation of the water-blocking gel layer, modified fly ash and modified coal gangue are not added to the modified coal-based solid waste suspension, and ethyl acetate of equal mass is used instead of modified fly ash and modified coal gangue.

[0187] Test method:

[0188] Compressive strength test: In accordance with GB / T 2567—2008 standard, the compressive strength of the composite gel materials prepared in Examples 1-4 and the water-blocking gel layer materials prepared in Examples 1-4 were tested after being sealed at room temperature for 7 days.

[0189] Limiting oxygen index (LOI) test: The limiting oxygen index (LOI) of the water-blocking gel layer materials prepared in Examples 1-4 was tested using a critical oxygen index meter according to GB / T 2406.2—2009.

[0190] Shrinkage rate test of the solidified body: The solidified body (i.e., the water-blocking gel layer material prepared above) sample was cut into pieces of 20.0mm × 20.0mm × 20.0mm in size, and its mass m was measured. a It was placed in an 80℃ electric heating blast dryer and tested every hour. Its mass was then removed and weighed. After reaching a constant weight, it was removed and its mass was measured as m. b The formula for calculating the shrinkage rate of a solidified body is as follows: R1=(m a -m b ) / m a .

[0191] Water absorption rate test of the solidified body: The solidified body sample (i.e., the water-blocking gel layer material prepared above) was cut into pieces with a volume of 20.0mm × 20.0mm × 20.0mm. After drying in an oven to constant weight, its mass m1 was recorded. The sample was then immersed in distilled water at 20℃ for 8 hours. Every 1 hour, the sample was taken out, the surface moisture was dried, and its mass was weighed. After the mass remained constant, the mass was weighed again and its mass m2 was recorded. The formula for calculating the water absorption rate of the solidified body is as follows: R2=(m2-m1) / m1.

[0192] The test results of the water-blocking gel layers prepared in the above embodiments and comparative examples are shown in Table 3.

[0193] Table 3

[0194]

[0195] The comparison of the compressive strength of the composite gel material prepared in the example with that of the composite gel material sealed at room temperature for 7 days shows that the composite gel material prepared in this invention contains water and alkali, which will further undergo a hydration reaction of fly ash, coal gangue and water during the subsequent standing process, thereby further increasing the compressive strength of the composite gel material.

[0196] The limiting oxygen index of the water-resistant gel layer prepared in the examples shows that the composite gel material of the present invention has a good flame-retardant effect.

[0197] The sealing principle of polyurethane gel materials mainly involves the reaction of NCO in the system with water, rapidly solidifying to generate a large amount of gel solidified material. Because the solidified material contains a large amount of water, drying and shrinkage are inevitable during use. If the shrinkage rate of the solidified material is large, re-leakage may occur. The standard for detecting re-leakage is "solidified material water absorption rate > solidified material shrinkage rate". In the embodiments of this invention, the water absorption rate of the solidified material of the coal-based solid waste and polyurethane composite gel is greater than the solidified material shrinkage rate, indicating that the coal-based solid waste and polyurethane composite gel prepared in the embodiments of this invention will not experience re-leakage during use. Furthermore, the solidified material shrinkage rate of the coal-based solid waste and polyurethane composite gel of this invention is lower than that of the comparative sample. A smaller solidified material shrinkage rate helps reduce the distance between the solidified material shrinkage and the bonding matrix, thereby improving the overall performance and durability of the material.

[0198] As can be seen from the results of Example 1 and Comparative Examples 1-4, only with the combined action of the four types of gels in the water-blocking gel layer of the present invention can a water-blocking gel layer with good water-blocking effect be obtained. This water-blocking gel layer can fully absorb water from the support layer or elsewhere. Even if it cannot absorb it, due to its water-blocking and water-stopping properties, it can also prevent excessive water from entering the coal gangue layer, thereby avoiding the large-scale leaching of metal ions from the coal gangue layer due to water penetration and environmental pollution.

[0199] In addition, the water-resistant gel layer has good compressive strength and is not easily damaged, and it also has a good flame retardant effect. Applying it above the coal gangue layer can provide secondary protection to reduce the combustion and pollution of the coal gangue layer.

[0200] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art should understand that various modifications or variations that can be made without creative effort based on the technical solutions of the present invention are still within the protection scope of the present invention.

Claims

1. A method for mine pit restoration, characterized in that, Includes the following steps: (1) Lay a seepage-proof layer at the bottom of the leveled mine pit; (2) Lay a coal gangue layer on the seepage barrier layer, and then lay the first support layer on the coal gangue layer; (3) Inject a layer of grouting base liquid into the first support layer, and add a portion of the volume of water-based crosslinking liquid to the grouting base liquid in sequence for reaction, and alkaline solution containing fly ash for reaction, and finally add the remaining water-based crosslinking liquid to obtain a water-blocking gel layer. (4) Lay a second support layer 10-20cm above the water-resistant gel layer and install a drainage pipe between the two support layers; (5) Lay a soil layer on the second support layer and spray crusting material to complete the mine pit repair.

2. The mine pit restoration method according to claim 1, characterized in that, In step (1), the impermeable layer consists of a clay layer, a bentonite layer and a polyethylene LDPE membrane layer from bottom to top; the thickness of the clay layer is 30-40cm; the thickness of the bentonite layer is 20-30cm; and the thickness of the polyethylene LDPE membrane layer is 1.0-1.5mm.

3. The mine pit restoration method according to claim 1, characterized in that, In step (3), the formation of the water-blocking gel layer includes: adding an aqueous crosslinking liquid in two stages. The first stage involves adding 75%-90% of the volume of the liquid to trigger the initial gelation reaction. Then, an alkaline solution containing fly ash is added to fill the pores. Finally, the remaining crosslinking liquid is added to complete the curing process.

4. The mine pit restoration method according to claim 1, characterized in that, The grouting base liquid in step (3) is obtained by mixing hydrophilic polyurethane prepolymer and modified coal-based solid waste suspension evenly; wherein the mass ratio of hydrophilic polyurethane prepolymer to modified coal-based solid waste suspension is 1:(0.1-0.3).

5. The mine pit restoration method according to claim 4, characterized in that, The modified coal-based solid waste suspension includes silane coupling agent-modified fly ash, coal gangue, and ethyl acetate / methyl acetate; the mass ratio of unmodified fly ash to unmodified coal gangue is 1:(1.2-1.5); the mass ratio of modified fly ash to organic solvent is (1-2):100; the hydrophilic polyurethane prepolymer includes polyether polyol and isocyanate; the molar ratio of -NCO of the isocyanate to -OH of the polyether polyol is (5-8):

1.

6. The mine pit restoration method according to claim 1, characterized in that, The drainage pipes are evenly distributed between the first support layer and the second support layer, with a pipe spacing of 1-2m, and are used to guide water that has not been absorbed by the water-blocking gel layer.

7. The mine pit restoration method according to claim 1, characterized in that, The first and second support layers are both made by mixing and curing fly ash, lime, cement in a mass ratio of (45-70):(18-30):(15-20) with water glass, with a thickness of 10-20cm, wherein the mass of water glass is 4-7% of the mass of cement.

8. The mine pit restoration method according to claim 1, characterized in that, The aqueous crosslinking liquid mentioned in step (3) includes sodium alginate and water, and the mass ratio of sodium alginate to water is 1:100-150; The mass ratio of the hydrophilic polyurethane prepolymer to the aqueous crosslinking liquid in the grouting base liquid is 1:(15-25); The alkaline solution containing fly ash comprises fly ash, alkali, and ethanol; wherein the mass ratio of fly ash to alkali is 1:(4-8); the concentration of alkali in ethanol is 2-4 mol / L; and the alkali is sodium hydroxide or potassium hydroxide. The mass ratio of the hydrophilic polyurethane prepolymer in the grouting base liquid to the alkaline solution containing fly ash is 1:(0.5-1).

9. The mine pit restoration method according to claim 1, characterized in that, In step (5), the thickness of the soil layer is 100-150cm, and the amount of the crust material sprayed is 2%-3% of the soil mass, forming a wind-erosion resistant surface layer with a thickness of 0.5-1mm.

10. The mine pit restoration method according to claim 1, characterized in that, The water-blocking gel layer comprises a quadruple gel network: A gel formed by the reaction of S1 polyurethane prepolymer with water; Electrite / CSH gel generated from the hydration of S2 coal-based solid waste; S3 mineral gel formed by the reaction of fly ash and alkaline solution in the pores. S4 sodium alginate crosslinked with calcium ions gel.